PDK4 drives metabolic alterations and muscle atrophy in cancer cachexia - Pin, Fabrizio; Novinger, Leah J; Huot, Joshua R; Harris, Robert A; Couch, Marion E; O'Connell, Thomas M; Bonetto, Andrea (The FASEB journal, 2019)
Cachexia is frequently accompanied by severe metabolic derangements, although the mechanisms responsible for this debilitating condition remain unclear. Pyruvate dehydrogenase kinase (PDK)4, a critical regulator of cellular energetic metabolism, was found elevated in experimental models of cancer, starvation, diabetes, and sepsis. Here we aimed to investigate the link between PDK4 and the changes in muscle size in cancer cachexia. High PDK4 and abnormal energetic metabolism were found in the skeletal muscle of colon-26 tumor hosts, as well as in mice fed a diet enriched in Pirinixic acid, previously shown to increase PDK4 levels. Viral-mediated PDK4 overexpression in myotube cultures was sufficient to promote myofiber shrinkage, consistent with enhanced protein catabolism and mitochondrial abnormalities. On the contrary, blockade of PDK4 was sufficient to restore myotube size in C2C12 cultures exposed to tumor media. Our data support, for the first time, a direct role for PDK4 in promoting cancer-associated muscle metabolic alterations and skeletal muscle atrophy.-Pin, F., Novinger, L. J., Huot, J. R., Harris, R. A., Couch, M. E., O'Connell, T. M., Bonetto, A. PDK4 drives metabolic alterations and muscle atrophy in cancer cachexia.